The speech and language protocol : an assessment tool for early years - LoPresti, Stephanie (New York, NY : Routledge, 2025)
"This valuable book addresses the common problems faced by speech-language pathologists, offering solutions and strategies for more effective service delivery. LoPresti introduces 'The Protocol', a child development-based approach that merges principles from developmental psychology and speech-language pathology. The book covers a wide range of speech and language issues, including receptive, expressive, pragmatic, feeding, and play development, making it a versatile resource for clinicians. It is designed to be easy to use, with movable elements that adapt to a child's progress from short to long-term milestones and goals. It emphasizes the concept of the zone of proximal development, ensuring that clinicians work with clients just above their current level of functioning, leading to meaningful progress. Accompanied by downloadable worksheets to assess progress, it will be an essential resource for all speech and language pathologists, particularly those working with young children. It will also be useful to students and educators in the field of speech-language pathology seeking evidence-based strategies for working with clients, as well as healthcare professionals, researchers, and educators interested in child development and language acquisition"--
Foundational Information -- Piaget's Stages -- Parten's Social Stages of Play -- Cognitive Milestones -- Receptive Language Milestones -- Expressive Language Milestones -- Motor Speech Progressions -- Speech Sounds & Phonological Norms -- Swallowing & Feeding Milestones -- Social-Emotional Milestones -- Social Communication Benchmarks -- Brown's Stages of Morphological & Syntactic Development.
Keywords: Language acquisition; Children; EDUCATION / Special Education / Communicative Disorders; HEALTH & FITNESS / Hearing; PSYCHOLOGY / Neuropsychology